Self-dealing by directors / Vivien Chen Jean Hui - Vivien, Chen Jean Hui (2001)
Directors hold a significant position of influence over the assets and affairs of the company. This position gives rise to the potential for the misuse of the company's assets for the directors' own gain. In an era of marked growth of the significance of companies, there has been an increasing awareness of the need for protection of the company against abuse by directors.In recognition of the position of influence held by directors, equity has regarded directors as fiduciaries. Fiduciary duties to the company have been imposed on directors, specifically constraining self-dealing by directors.